Pengaruh Metode Drill Dan Practice (D&P) Terhadap Peningkatan Kemampuan Berpikir Kreatif Siswa Sekolah Dasar Ditinjau Dari Kemampuan Awal Matematis - Takaria, Johannis; Sahusiwa, Yuyun (Jurnal PGSD, 2020)
Mathematical creative thinking skill is important for elementary school students to have so they can be actively involve in solving challenging mathematical problems. Related to this, the purpose of the study is to determine the effect of Drill and Practice (D&P) methods on improving student mathematical creative thinking abilities in terms of their initial Prior-Ability on Mathematics (PAM). The study used a Quasi Experiment method with the type of One Group Pre test-Post test Design and involved 22 students as a research sample that were selected pro positively. To analyze the increase in mathematical creative thinking abilities used Ngain. The result showed that there was an influence of the D&P method on improving student mathematical creative thinking abilities in terms of PAM. Further tests using the Post Hoc Test showed that high PAM level >< moderate there was no difference, while high PAM >< low and moderate >< low there was a difference. Each PAM level achieved an increase in the medium category. The increase is due to the effectiveness of the D&P method. The D&P method can trigger an increase in student creative thinking skills because students Practice working on questions and Practice on contextual problems. This process allows students to explore their creative thinking abilities